Study on the effect of modified Liu-an decoction on Th1/Th2 function in Guinea pigs with cough variant asthma through the Notch signal pathway - Fangwei Xu; Jian Deng; Ningning Zhang; Kimberly XinTing Leow; Panpan Li; Chen Lu; Yuhang Chen; Ye Zhang; Liqun Wu (PLoS ONE, 2025)
Objective To explore the effects and mechanism of Modified Liu-an Decoction (MLAD) on Th1/Th2 function and the Notch signaling pathway in guinea pigs with cough variant asthma (CVA). Methods 60 SPF Hartley guinea pigs were randomized into six groups (n = 10): the blank control group, model group, montelukast sodium group (MS group), as well as MLAD group of low-dose, mid-dose and high-dose. Intraperitoneal injection of ovalbumin, aluminum hydroxide sensitization, and nebulized inhalation of ovalbumin were performed in all guinea pigs of non-blank control groupto induce CVA. Cough frequency and airway resistance were recorded. The chronic inflammatory infiltration in the airways was detected by using HE and Masson staining smears. The IL-2, IL-4, IL-12, and IL-13 levels were measured by enzyme-linked immunoassay (ELISA). The expression of Delta, Jagged1, Notch1, and NICD proteins in the lung tissues were analyzed by Western blot. Results In terms of airway sensitivity, coughing time and airway resistance were reduced in the MLAD and MS groups compared to the model group (P < 0.05). MLAD reduced the inflammatory infiltration in the lungs of CVA guinea pigs compared with the model group (P < 0.05).For cytokines in BALF, the contents of IL-2 and IL-12 were increased in the MS group and each dose group of MLAD compared with the model group, and the contents of IL-4 and IL-13 were decreased compared with them.The contents of IL-12 were significantly different in each dose group of MLAD compared with the model group; the contents of IL-2 and IL-4 differed with increasing concentrations of MLAD. 4 content with increasing MLAD concentration, the more significant difference. IL-13 content decreased significantly in the MLAD low dose group compared with the model group (P < 0.05). In the serum cytokine model group IL-2, IL-12, IL-13 content were significantly higher than the blank group, IL-4 content was lower than the blank group, and the difference between each intervention group and the model group was not regular. The expression levels of Jagged1, Notch, and NICD proteins in the CVA guinea pigs in the MS group and the low-dose MLAD group were decreased compared with those in the model group, and the expression of Delta1 protein was increased compared with that in the model group (P < 0.05). Conclusion The addition of Liuan Decoction to the lungs can clear lungs and remove heat and strengthen the spleen to resolve phlegm, congestion, edema degree, reduce airway inflammation, and at the same time can reduce peri-tracheal collagen deposition, effectively improve airway remodeling, by regulating the dynamic balance of Th1/Th2. The specific downstream regulatory mechanisms of Notch signaling pathway need to be explored in further studies.